Penyelesaian Kasus Kepemimpinan Perempuan Di Indonesia Dalam Pemikiran Abu Muhammad Izz Al-Din Abdul Aziz Ibn Abdi Al-Salam - Hasiolan Nasution; Anna Navita Syairoh (PT. Student Rihlah Indonesia, 2025)
Women's involvement in the public sphere is still an issue that requires in-depth study, especially related to women's abilities to become a community leader. This view is considered to have the legitimacy of the Qur'an, so it is necessary to look again at the view of the mufassir as the holder of authority in the study of the verses of the Qur'an. Therefore, the purpose of this article is to analyze the thoughts of 'Izz al-Din bin Abdi Salam regarding women's leadership. The issue of women's leadership has always been a growing study and not a few that make it a central issue in political battles. To achieve this goal, the author of this article uses a qualitative method, namely library research. The source of the data is taken from a book written by 'Izz al-Din with the title al-Qawā'id al-Kubrā (Qawā'id al-Ahkām fī Ishlāh al-Anām. The data was analyzed using the content analysis method. The findings in this article reveal that with the concept of maslahat offered by 'Izz al-Din, gender is not the main requirement to become a leader but what is most important is one's capacity and integrity as well as the ability to uphold leadership principles such as justice. The above results can be a scientific basis for women, both for policymakers and the general public regarding their involvement in the public sphere.